The thank you book - Willems, Mo. (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2016)
"Piggie is determined to thank everyone she knows, but Gerald thinks she will forget someone important"--Provided by publisher.
1.4
K-3.
K-3
Keywords: Animals -- Juvenile fiction; Elephants -- Juvenile fiction; Friendship -- Juvenile fiction; Gratitude -- Juvenile fiction; Swine -- Juvenile fiction; Animals -- Fiction; Elephants -- Fiction; Friendship -- Fiction; Gratitude -- Fiction; Pigs -- Fiction; Animals -- Fiction; Elephants -- Fiction; Friendship -- Fiction; Gratitude -- Fiction; Pigs -- Fiction; Humorous fiction; Readers (Publications)